Educational Resources And Gender Norms: An examination of the Actiotope Model of Giftedness and social gender norms on achievement. (3rd July 2021) - Lafferty, Kate; Phillipson, Shane N.; Costello, Shane
ABSTRACT: The expectancy-value theory of achievement performance and related decisions identifies the various factors that affect achievement levels. The Actiotope Model of Giftedness describes learning and educational resources necessary for high achievement. This study investigates the relationship between these categories of resources and achievement. As social gender norms have been shown to influence decisions in a range of contexts, including college majors, the influence of resources on conformity levels is also examined. We investigated these relationships amongst undergraduate university students from Australia (n = 976) using the Questionnaire of Educational and Learning Capitals (QELC) and Conformity to Feminine Norms-45 (CFNI-45) and Conformity to Masculine Norms-46 (CMNI-46). Results from structural equation modeling indicated that educational capital plays an important role in establishing learning capital, that in turn leads to decreased levels of conformity. This has implications when supporting high ability students, not just in terms of developing resources, but also regarding non-traditional postsecondary fields of study.